Psychological Characteristics and Health Behavior for Juvenile Delinquency Groups - Fangbin Song; Ruihua Li; Wei Wang; Shenyu Zhang (Occupational Therapy International)
The related literature is studied to explore the psychological characteristics of juvenile delinquency groups and implement their psychological characteristics model for the intervention of health behavior. Drawing on the results of current literature research, the Youth Psychological Characteristics Crime Prevention Questionnaire (YPPQ) was compiled, which can be simply referred to as the Crime Prevention Questionnaire. The whole psychological characteristics of juvenile delinquency are analyzed by means of a questionnaire. Firstly, the YPPQ scores of different groups were compared, and a structured interview was conducted on the reasons for the crime of the problem youth group. Secondly, data analysis was carried out on the results of questionnaires and interviews, and the psychological characteristics of juvenile delinquency were summarized. A “mixed hierarchical intervention model” was proposed to intervene in the mental health behavior of juvenile delinquency groups, and corresponding intervention strategies were also proposed. The results reveal that through the questionnaire survey, the educational background of juvenile subjects was generally distributed in middle school, the number of juveniles with primary school education was less than 30% of the juvenile delinquency groups, the middle school education accounted for more than 60% of the juvenile delinquency groups, and the approximate age was about 18 years old. The largest number in each group were adolescents with secondary school education, indicating the importance of psychological education on crime prevention for adolescents in secondary school. By comparing the YPPQ test scores of different groups, the adolescent group has higher test scores than the juvenile delinquency groups in five of the dimensions. Through the comparative analysis of the YPPQ test results of the juvenile delinquency groups, the problem youth group, and the normal youth group, it is found that the YPPQ has high reliability and validity, so its detection and evaluation are highly feasible. By comparing the odds ratio (OR) of each question in the YPPQ test between the experimental group and the control group, it is found that the psychological characteristics of the experimental group are significantly affected by family, school, and even society. Finally, it proposes a “mixed hierarchical intervention model” for juvenile delinquency to intervene in health behaviors. The purpose is to provide some research ideas for the study of the psychological characteristics of juvenile delinquency groups and to put forward some suggestions for the prevention of juvenile delinquency and the intervention of health behavior.